Antioxidant neoagarooligosaccharides (NAOs) and dietary fiber production from red algae Gracilariopsis lemaneiformis using enzyme assisted one-step process. (April 2022) - Song, Tao; Liu, Ling; Tang, Qianlin; Xiang, Shengwei; Wang, Binkai; Zhang, Shuzhen; Wang, Xinrong; Chu, Yiwen; Luo, Dan; Lin, Jiafu
Abstract: Red algae are the most widely cultivated macroalgae crops in aquaculture, and they are often directly ingested in a daily diet and used as raw material for food hydrocolloid extraction. The current dilemma regarding red algae exploitation involves their low added value. Here, we propose using an enzyme-assisted one-step process (ESOP) to convert homogenized Gracilariopsis lemaneiformis to high valued neoagarooligosaccharides (NAOs) and dietary fibre simultaneously. First, we optimized the hydrolysis process (the following conditions were used: 15 g wet G. lemaneiformis /150 mL buffer, 15 min homogenization and 25 U load enzyme amount) to produce 17.13 mg crude NAOs. Second, TLC, CNMR and MALDI-TOF-MS were performed, and the results indicated that NAOs may be modified by a variety of substitutions. Meanwhile, NAOs showed antioxidant activities in the DPPH, ABTS and free radical scavenging experiments at different concentrations. Third, dietary fibre concentrates were prepared and shown to have 60.78% dietary fibre, 4.19% protein, 8.43% moisture and 2.06% ash contents. Dietary fibre concentrate might have great potential in the food industry because of its physiological properties, including its thermostability at 30–1150 °C, water holding capacity (24.20 g/g) and oil holding capacity (8.26 g/g). Therefore, G. lemaneiformis was firstly converted into high value-added NAOs and dietary fibre at the same time using ESOP. This process was environmentally friendly and preserved the active compounds, and therefore provided clues for the further comprehensive use of other seaweeds or plants containing gel-like polysaccharides. Graphical abstract: Image 1 Highlights: Gracilariopsis lemaneiformis is firstly used to produce neoagarooligosaccharides (NAOs) and dietary fibre simultaneously. NAOs have antioxidant activities in DPPH, ABTS and free radical scavenging experiments. Dietary fibre from G. lemaneiformis has water holding capacity and oil holding capacity at the same time. Enzyme assisted one step process is a low-cost and environmental friendly approach.